Influence of betaine consumption on strenuous running and sprinting in a hot environment - Armstrong, L. E.; Casa, D. J.; Roti, M. W.; Lee, E. C.; Craig, S. A. S.; Sutherland, J. W.; Fiala, K. A.; Maresh, C. M. (The Journal of Strength and Conditioning Research, 2008)
This investigation evaluated the effects of a nutritional supplement (the organic osmolyte betaine) in rehydration solutions, with and without carbohydrate and electrolytes. Ten male runners ((mean ± SD) age, 20 ± 2 years; weight, 70.6 ± 6.8 kg; maximal aerobic power, 63.5 ± 4.1 mL O2/kg·min) dehydrated to -2.7% of body weight. They next rehydrated to -1.4% of body weight by consuming 1 L fluid during each of four experiments (double-blind, randomized, cross-over design): flavored, non-caloric water (W); W + 5 g/L betaine (W+B); 6% carbohydrate-electrolyte fluid (C); or C + 5 g/L betaine (C+B). Subjects then performed prolonged treadmill running (75 minutes at 65%[latin capital V with dot above]o2max) plus a performance sprint to volitional exhaustion (3.1-3.8 minutes at 84%[latin capital V with dot above]o2max) in an environmental chamber (31.1°C, 88.0°F). Only W versus W+B and C versus C+B statistical comparisons were germane to the research questions. Observations indicated that rehydration with fluids containing betaine resulted in significant differences (p < 0.05) of plasma volume, oxygen consumption, plasma lactate concentration, and thermal sensation. The present experiments did not support the use of betaine to improve sprint duration, but nonsignificant trends occurred when betaine trials were compared with non-betaine trials (mean C+B > C by 32 seconds, +16%; mean W+B > W by 38 seconds, +21%). We interpret the increases of both aerobic and anaerobic metabolism (C+B > C) to mean that further investigation of betaine as a nutritional supplement, using other types of exercise, is warranted.